Les rôles respectifs de l'État et du citoyen - Oreja, Marcelio (Les Cahiers de droit, 1987)
At first glance, national sovereignty and the respect of Human Rights seem, since the first is unachievable without detriment to the second, irréconciliable. When a country binds itself through an international agreement to respect Human Rights it may still violate these accords with impunity by hiding behind the sacred principle of non-interference, a precept often invoked by other countries to justify their passivity. For the author, this pessimistic view does not, however, take into consideration the fact that evolution in the safeguards to human rights has only come about with the consent of sovereign nations. There are few countries in the world today who flagrantly disregard Human Rights without feeling the need to justify themselves. It may now be said that there is a beginning of virtue in the reality of international relations. There may certainly exist conflict between the exercice of sovereignty and the respect of Human Rights, but in democratic countries, this does not constitute an absolute paradox. It is the responsibility of the people governed to make good their rights by exerting the necessary pressure on their government when it does not have a tendency to liberalize its policies. This is because, in the end, Human Rights do not belong to the State but to the people.